Human Relations Training for Middle Management: A Reply - Hand, Herbert H.; Slocum, John W. (Academy of Management Journal, 1971)
A letter to the editor is presented in response to a criticism of the article ?Human Relations Training for Middle Management: A Field Experiment,? published in the June 1971 issue.